1986
DOI: 10.1111/j.1600-0447.1986.tb02692.x
|View full text |Cite
|
Sign up to set email alerts
|

Delusional depression: phenomenology and response to treatment

Abstract: In a prospective study, the authors compared 22 delusional and 36 non-delusional depressive patients with respect to demographic and clinical variables, personality, and response to treatment. Delusional depressives had a higher total score than non-delusional depressives on Hamilton's Rating Scale for Depression, as well as a higher score for depressed mood and psychomotor retardation. The type of treatment failed to differentiate the two groups as to outcome at discharge. However, six of the seven delusional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Late-onset PMD may require different somatic therapies, clinical management and closer follow-up. This ®nding contradicts studies of mixedage depressives (Guze et al, 1975;Zis and Goodwin, 1979;Winokur et al, 1980;Charney and Nelson, 1981;Glassman and Roose, 1981;Frances et al, 1981;Fragos et al, 1983;Brown et al, 1984;Lykouras et al, 1986;Jeste et al, 1996), which did not observe an association between PMD and onset of depression. Nevertheless, Hori et al (1993), found that PMD patients had a later age of depression onset.…”
Section: Discussionmentioning
confidence: 51%
“…Late-onset PMD may require different somatic therapies, clinical management and closer follow-up. This ®nding contradicts studies of mixedage depressives (Guze et al, 1975;Zis and Goodwin, 1979;Winokur et al, 1980;Charney and Nelson, 1981;Glassman and Roose, 1981;Frances et al, 1981;Fragos et al, 1983;Brown et al, 1984;Lykouras et al, 1986;Jeste et al, 1996), which did not observe an association between PMD and onset of depression. Nevertheless, Hori et al (1993), found that PMD patients had a later age of depression onset.…”
Section: Discussionmentioning
confidence: 51%
“…We conclude that second ary depression is less likely to be accompa nied by psychosis than primary depression. This finding is what one might anticipate if psychotic features are taken as an indication of illness severity, as several authors have suggested [18,22,23],…”
Section: Primary Versus Secondary Affective Disordersmentioning
confidence: 54%
“…A number of studies have reported that certain individual symptoms in PMD patients tend to more prevalent or severe, including suicidality [18], psychomotor disturbance (agitation or retardation) [12,19], insomnia [20], guilt [17], and cognitive impairment [21]. PMD tends to be associated with greater overall depression severity compared to NMD; however, some studies have shown that differences between PMD and NMD patients exist in many cases even after controlling for the influence of other symptoms [13,17].…”
mentioning
confidence: 99%